Differences in Lower Extremity Movement Quality by Level of Sport Specialization in Cadets Entering a United States Service Academy. (November 2021) - Venrick, CPT Connor B.; Miraldi, Story F.; DiStefano, Lindsay J.; Peck, Karen Y.; Posner, LTC Matthew A.; Houston, Megan N.; Padua, Darin A.; Marshall, Stephen W.; Cameron, Kenneth L.
Background: Sport specialization in youth athletes is associated with increased risk for musculoskeletal injury; however, little is known about whether sport specialization is associated with lower extremity movement quality. The purpose of this study was to examine differences in lower extremity movement quality by level of sport specialization in US Service Academy cadets. Hypothesis: Cadets who report an increased level of sport specialization would have a lower level of movement quality than those who are less specialized. Study Design: Cross-sectional analysis from an ongoing prospective cohort study. Level of Evidence: Level 3. Methods: Cadets completed the Landing Error Scoring System (LESS) and a baseline questionnaire evaluating level of sport specialization during high school. Data were analyzed using separate 1-way analysis of variance models. Results: Among all participants (n = 1950), 1045 (53.6%) reported low sport specialization, 600 (30.8%) reported moderate sport specialization, and 305 (15.6%) reported high sport specialization at the time of data collection during the first week. Ages ranged from 17 to 23 years. Men (1491) and women (459) reported comparable specialization levels ( P = 0.45). There were no statistically significant differences in lower extremity movement quality by level of specialization for all subjects combined ( P = 0.15) or when only men were included in the analyses ( P = 0.69). However, there were statistically significant differences in movement quality by level of specialization in women ( P = 0.02). Moderately specialized women had the best movement quality (mean, 4.63; SD, 2.21) followed by those with high specialization (mean, 4.90; SD, 2.08) and those with low levels of specialization (mean, 5.23; SD, 2.07). Conclusion: Women reporting moderate sport specialization had improved movement quality and significantly better LESS scores compared to those with high/low specialization. Clinical Relevance: Athletes, especially women, should be encouraged to avoid early sport specialization to optimize movement quality, which may affect injury risk.